Perancangan Antarmuka Sistem Informasi Smart Classroom Menggunakan Metode Design Thinking - Yessica Nur Ameilia Pratiwi; Maulina Aurelly Putri; Muhamad Firmansyah (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2022)
Advances in information technology today have provided many benefits in all fields, especially in education. Utilization in the field of education as an example is the construction of an information system website for the education system and information technology study program. With the use of information technology allows the implementation of learning to be easier and more comfortable. In making an information system for this study program, what will be included in the system includes information about student lists, subjects, attendance, learning materials, events, discussion groups. In this system, of course, only residents of the system and information technology study program can access it. The method used is design thinking which aims to solve problems and create many ideas for the development of study program information systems.